2006
DOI: 10.1021/es052184t
|View full text |Cite
|
Sign up to set email alerts
|

Reoxidation Behavior of Technetium, Iron, and Sulfur in Estuarine Sediments

Abstract: Technetium is a redox active radionuclide, which is present as a contaminant at a number of sites where nuclear fuel cycle operations have been carried out. Recent studies suggest that Tc(VII), which is soluble under oxic conditions, will be retained in sediments as Fe(III)-reducing conditions develop, due to reductive scavenging as hydrous TcO2. However, the behavior of technetium during subsequent reoxidation of sediments remains poorly characterized. Here, we describe a microcosm-based approach to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
111
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 46 publications
12
111
2
1
Order By: Relevance
“…11 Bioimmobilization efforts have also been employed in the efforts to reduce and stabilize TcO 4 -in soil by natural organic matter. 8,12 In these studies chemical reduction 7,13 and microbial reduction 5,14 led to the formation of TcO 2 2 O. However, the reduced 99 Tc IV in the form of the amorphous oxides also reoxidizes back to the mobile Tc VII O 4 -anion.…”
Section: Introductionmentioning
confidence: 99%
“…11 Bioimmobilization efforts have also been employed in the efforts to reduce and stabilize TcO 4 -in soil by natural organic matter. 8,12 In these studies chemical reduction 7,13 and microbial reduction 5,14 led to the formation of TcO 2 2 O. However, the reduced 99 Tc IV in the form of the amorphous oxides also reoxidizes back to the mobile Tc VII O 4 -anion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when considering Tc behaviour in the environment, it is also necessary to explore the potential for oxidative remobilization of Tc(IV). Reoxidation of immobilized radionuclides in contaminated aquifers could occur via transport of oxygenated waters through the sediments, water table fluctuations, or disturbance of the geosphere by construction or erosion (Burke et al, 2006;Wu et al, 2007). Furthermore, reoxidation caused by nitrate, a common pollutant found at nuclear facilities, is also a potential route to radionuclide reoxidation via, for example, biologically mediated Fe(II)-oxidation coupled to NO 3 À reduction (Burke et al, 2006;Geissler et al, 2011;Morris et al, 2008;Senko et al, 2005;Wu et al, 2010;Law et al, 2010b;Law et al, 2011).…”
mentioning
confidence: 99%
“…Reoxidation of immobilized radionuclides in contaminated aquifers could occur via transport of oxygenated waters through the sediments, water table fluctuations, or disturbance of the geosphere by construction or erosion (Burke et al, 2006;Wu et al, 2007). Furthermore, reoxidation caused by nitrate, a common pollutant found at nuclear facilities, is also a potential route to radionuclide reoxidation via, for example, biologically mediated Fe(II)-oxidation coupled to NO 3 À reduction (Burke et al, 2006;Geissler et al, 2011;Morris et al, 2008;Senko et al, 2005;Wu et al, 2010;Law et al, 2010b;Law et al, 2011). Recent experimental work on sediments suggests that Tc associated with Fe(II)-bearing sediments is recalcitrant to reoxidation even though significant reoxidation of Fe(II) to Fe(III) occurs during both air and nitrate reoxidation (Burke et al, 2006;Fredrickson et al, 2009;Geissler et al, in press;Jaisi et al, 2009 .…”
mentioning
confidence: 99%
“…A number of experiments that examined the reduction and retention of 99 Tc in natural sediments whose oxidation states have been artificially altered (Burke et al 2006, Burke et al 2005, Fredrickson et al 2004, Morris et al 2008, Zachara et al 2007) yielded some interesting and useful results for secondary 99 Tc sequestration. Reduction of Tc(VII) to Tc(IV) by ferrous iron (Fe(II)) in solution is sluggish (homogeneous kinetics), even though the reaction…”
Section: Goethitementioning
confidence: 99%
“…The atomic structure of goethite, recently determined by Yang et al (2006), is shown in Figure 2.5. On the other hand, examining the reduced run products with X-ray absorption spectroscopy (XAS) methods (briefly described in Appendix A) has revealed that the 99 Tc-bearing phase is a separate, reduced Tc(IV) oxide phase and may not be substituting for Fe(III)-O in the host ferric oxyhydroxide phase (Burke et al 2006, Fredrickson et al 2004, Fredrickson et al 2009, Morris et al 2008, Peretyazhko et al 2008a, Watson et al 2001, Wharton et al 2000, Zachara et al 2007). In the most detailed study, Fredrickson and coworkers (Fredrickson et al 2009) found that Tc(IV)O 2 -like compounds could exist in a number of states, including physically separate phases or those that are inter-grown with Fe(III)-O compounds.…”
mentioning
confidence: 99%